Exiting Financial Repression : The Case of Ethiopia - Chauffour, Jean-Pierre; Gobezie, Muluneh Ayalew (World Bank, Washington, DC, 2019)
Ethiopia's framework for managing its monetary and foreign exchange policy has relied on some standard instruments of financial repression. Over time, the framework has led to the buildup of large macro-financial imbalances. Exiting financial repression while maintaining macroeconomic stability would require solid control over the macro-financial flows and good anticipation of the immediate financial effects of the reform. The paper presents and quantifies such a gradual liberalization reform scenario of Ethiopia's monetary and foreign exchange system.